Identifying gender disparities on the time to repay microfinance group loans: Evidence from Mexico - Enrique Bátiz-Zuk; Alexa González-Holden (Banco de México, 2023)
This paper investigates how gender disparities affect the time to repay group micro-finance loans using survival analysis and hazard decomposition techniques. We also control for the effect of the COVID-19 pandemic on the time needed by micro-finance loan borrowers to repay. We use a large sample of bank microfinance group loans from August 2017 to August 2021. Despite the fact that female borrowers' overall default rate is smaller, our unconditional estimates show that female borrowers default almost the equivalent of three consecutive installments earlier. Moreover, this result persists when we control for micro, industry, and macroeconomic factors. We also observe that the COVID-19 pandemic materialized as a spike in aggregate default rates that gradually reduced afterward. Our study identified a potential gender gap that has been understudied in the literature.
Keywords: C41; G21; J16; O12; O16; 330; Credit markets; Microfinance loan; Group lending; Gender; Survival analysis